2016
DOI: 10.1089/pho.2015.3997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO2Lasers on Dental Pulp Biology in Rats

Abstract: These results demonstrate that CO2 laser irradiation induces degeneration in the pulp tissue, which is then repaired by newly formed odontoblast-like cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Apart from dentine bridge formation, teeth from approximately 30 days post treatment in both groups showed irregular matrix formation close to the dentine walls, which seemed to be generated by the stimulation of laser energy (13)(14)(15). It is suggested that if an appropriate amount of stimulation by laser energy is applied to exposed pulp tissue, pulpal healing and repair may be enhanced.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Apart from dentine bridge formation, teeth from approximately 30 days post treatment in both groups showed irregular matrix formation close to the dentine walls, which seemed to be generated by the stimulation of laser energy (13)(14)(15). It is suggested that if an appropriate amount of stimulation by laser energy is applied to exposed pulp tissue, pulpal healing and repair may be enhanced.…”
Section: Discussionmentioning
confidence: 98%
“…The laser-irradiated pulp tissue exhibits various responses, which largely depend on irradiation settings such as wavelength, output power, waveform, pulse duration, interval time, focal spot size, energy density, total energy and others (2)(3)(4)(5)(6)(7)15,(20)(21)(22). Therefore, it is imperative to understand the precise specifications of laser devices when using a laser beam for treatments in the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol for qRT-PCR was performed according to Ser-Od et al 20) . Total RNA was obtained from each dish using the acid guanidium thiocyanate/phenol-chloroform method.…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr) Amentioning
confidence: 99%